2006
DOI: 10.1182/asheducation-2006.1.432
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Factor VIII Inhibitors: Pathophysiology and Treatment

Abstract: Hemophilia A is classically caused by a congenital deficiency of factor VIII, but an acquired form due to inhibitors to factor VIII (FVIII) typically presents later in life. Patients who develop such acquired factor VIII inhibitors may present with catastrophic bleeding episodes, despite having no prior history of a bleeding disorder. Though the disorder is rare, it is known to cause significant morbidity and mortality. This review will focus on what is currently known about acquired hemophilia A, its pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
205
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(212 citation statements)
references
References 64 publications
2
205
0
5
Order By: Relevance
“…The disease occurs when patients develop autoantibodies, or 'inhibitors', directed against the factor VIII (FVIII) clotting factor. Patients who develop such acquired FVIII inhibitors may present with catastrophic bleeding episodes, despite having no prior history of a bleeding disorder (Ma & Carrizosa, 2006). It is associated with considerable morbidity, as demonstrated by a survey of 215 non-haemophiliac patients who had developed inhibitors to FVIII; in this study major bleeding occurred in >80% of patients, with a mortality rate of approximately 20% (Green & Lechner, 1981).…”
Section: Disease Characteristicsmentioning
confidence: 99%
“…The disease occurs when patients develop autoantibodies, or 'inhibitors', directed against the factor VIII (FVIII) clotting factor. Patients who develop such acquired FVIII inhibitors may present with catastrophic bleeding episodes, despite having no prior history of a bleeding disorder (Ma & Carrizosa, 2006). It is associated with considerable morbidity, as demonstrated by a survey of 215 non-haemophiliac patients who had developed inhibitors to FVIII; in this study major bleeding occurred in >80% of patients, with a mortality rate of approximately 20% (Green & Lechner, 1981).…”
Section: Disease Characteristicsmentioning
confidence: 99%
“…Pericardial bloody effusion associated with factor VIII deficiency is a rare complication and may often be overlooked. Patients with factor VIII deficiency may develop serious and fatal complications, such as intracerebral hemorrhage, muscle bleeding, hematuria, epistaxis and gastrointestinal bleeding (4). The present study reported a life-threatening case of pericardial bloody effusion following cardiac tamponade and arrhythmia in a 39-year-old male whose factor VIII activity measured 14%.…”
Section: Discussionmentioning
confidence: 85%
“…1 3 Urology, 4 Radiotherapy and 5 Cardiology, Xiamen Chang Gung Hospital, Xiamen, Fujian 361000, P.R. China right ventricular anterior wall near to the apex, with evidence of right atrial and ventricular collapse and pericardial thickening.…”
Section: Case Reportmentioning
confidence: 99%
“…It is unclear whether the known and untreated chronic discoid lupus erythematodes is a predisposing factor for the development of acquired haemophilia A. Since rare cases of underlying non-systemic cutaneous diseases have been described in the literature [1,2], we assume that the discoid lupus in our patient might well be a predisposing disease.…”
Section: Discussionmentioning
confidence: 90%
“…Effective treatment involves not only the initial treatment of acute haemorrhage with factor VIII concentrates, a factor-VIII-bypassing-agent such as recombinant FVIIa or activated prothrombin complex concentrate but also the eradication of the inhibitor by 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 immunosuppression, plasmapheresis or immunoadsorption or a combination of these modalities [1,5,6].…”
Section: Introductionmentioning
confidence: 99%